The Effect of Leadership Style on Employee Commitment in the Mining Sector in Zimbabwe - Munyaradzi Chikove; Alphonce Shiri (Scientific Research Publishing, 2023)
The purpose of this study was to establish the effect of leadership style on employee commitment in the mining sector in Zimbabwe. The mining in- dustry in Zimbabwe has been extensively affected by the loss of key personnel in key areas such as engineering, metallurgy and geology among others. The loss of such vital employees in the mining sector has had a negative impact on output and consequently loss of the much-needed revenue to the Zimbab- wean economy. It is against this background that there was a need to establish the effect of leadership style on employee commitment in an endeavour to enhance job satisfaction. A quantitative approach was adopted in which con- venience sampling was employed. The main findings were that charismatic and inspirational leadership style has moderate to strong positive relationship with subordinate affective commitment to the organisation. Inspirational mo- tivation had a moderate positive correlation with affective commitment sig- nificant at (r = 0.46; p < 0.05) and Intellectual stimulation was found to have a strong correlation with affective commitment, significant at (r = 0.67; p < 0.05). Laissez faire leadership style displayed a very weak negative correlation between management by exception active with affective commitment, sig- nificant at (r = −0.012; p < 0.05). This study recommends that managers in the Zimbabwe mining sector should strive to use inspirational approaches in leading and involve employees in decision-making so as to raise the standards of efficiency and effectiveness of an organization and increase follower com- mitment.